Analysis Of Financing Procedures At The Kencana Ketahun Berkah Sejahtera Sharia Savings And Loan Cooperative (KKBS) Ketahun District North Bengkulu - Ummul Khair; Chairul Suhendra; Dharma Setiawan; Amir Mukadar (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Achievements in terms of providing financing to Cooperative members are notregardlessfrom the role of Cooperative administrators and managers in terms of carrying out/implementing proceduresproviding financing (loans) to members . ProcedureProviding financing is a rule or provisionmade by the management and approved by the Supervisor which is used as a guideline for the management/managers in carrying out their duties so that they can reduce one of the financing risks, namely avoiding or reducing bad financing (problems). With the existence of procedures for providing financing, it is hoped that the financing (loan) can be returned according to the agreement or it could also mean thatprocedureProviding financing requires members who receive financing facilities topay off the financing accordinglyagreementwithgiverloanalong with profits for the cooperative in the form of Ujrah, Margin or profit sharing according to the financing agreementset.ForThat adminis trator cooperative mustoperate procedur eproviding financing (loans) so thatits membersresponsibleresponsible for the financing (loan) received and making payments in accordance with the provisions or contracts that have been mutually agreed upon. The aim of this researcher is to: (a) know the procedureproviding financing to the Kecana Ketahun Berkah Sejahtra Savings and Loans and Sharia Financing cooperative (KKBS), (b) requirementswhat must be fulfilled by Kopeasi members to apply for financingon Cooperative . Save Kencana Sharia loans and financing for a Prosperous Blessing Year (KKBS) .MethodstudyWhichused in this research is qualitative. With this type of approachused is the phenomenology of procedures for providing financing toCooperativeSave Kencana Kertahun Berkah Sejahtera (KKBS) sharia borrowing and financing (KKBS) Ketahun District, North Bengkulu Regency .Andin formant Whichuse dismember Cooperative Andand management of the Savings CooperativeBorrowing and sharia financing for Kencana Ke Tahun Berkah Sejahtera (KKBS) . The results of this research show that the procedures for providing financing inCooperativeSave KKBS Sharia loans and financing are still availablethere islackfromstandardcredit granting procedures that always pay attention to the element of prudence. Meanwhilepro blemsmain Which thereisin procedure giving creditin Cooperative Save Kencana Ketahun Berkah Sejahtera sharia loans, Ketahun District, North Bengkulu Regency are: a) A photocopy of the KTP of the spouse of the member applying for financing (husband or wife) is not required. b) A letter of approval from the partner (husband or wife) is not required. there is proof of payment of PBB (Land and Building Tax) if the member provides collateral in the form of a Certificate of Ownership (SHM) d) There is no requirement for a power of attorney to guarantee if the collateral used is still in the name of another person e) There is no weighting or scoring in the method of determining a member's eligibility. using the 5 C method .